2016
DOI: 10.1136/bmjopen-2015-010063
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement in decision-making: a cross-sectional study in a Malaysian primary care clinic

Abstract: ObjectiveShared decision-making has been advocated as a useful model for patient management. In developing Asian countries such as Malaysia, there is a common belief that patients prefer a passive role in clinical consultation. As such, the objective of this study was to determine Malaysian patients’ role preference in decision-making and the associated factors.DesignA cross-sectional study.SettingStudy was conducted at an urban primary care clinic in Malaysia in 2012.ParticipantsPatients aged >21 years were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 14 publications
(17 reference statements)
1
42
0
Order By: Relevance
“…This finding was similar to a study carried out at a primary care clinic of a teaching hospital in Kuala Lumpur, which showed that most of the patients attending the clinic (51.9%) preferred SDM, followed by being passive (26.3%) and being active (21.8%) in decision-making. 14 Many studies have reported that most patients preferred SDM as being the most satisfactory. 32 34 Before seeing the doctor, the majority of the patients in this study perceived that their role in actual decision-making was similar to their preferences in treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was similar to a study carried out at a primary care clinic of a teaching hospital in Kuala Lumpur, which showed that most of the patients attending the clinic (51.9%) preferred SDM, followed by being passive (26.3%) and being active (21.8%) in decision-making. 14 Many studies have reported that most patients preferred SDM as being the most satisfactory. 32 34 Before seeing the doctor, the majority of the patients in this study perceived that their role in actual decision-making was similar to their preferences in treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“… 23 For ease of analysis, we categorized the active decision-making and SDM as an autonomous role, while the role of passive decision-making remained the same, similar to previous studies. 14 , 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An SDM approach suggested above is likely to be embraced by patients as a study done in our urban primary care setting showed that half of the patients preferred SDM over paternalism or informed patient roles. 35…”
Section: Box 2 Dual-layer Shared Decision Makingmentioning
confidence: 99%
“…[2] Patients can be either be passive, co-operative or active and Clinical decision-making models in the light of patient participation can be categorized as paternalistic model, in which patients play a passive role, professional-as-agent model, in which the doctor makes the decision for the patient, informed decision-making model in which necessary information is shared with the patient and he makes the decision at the end and shared decision-making model in which the patient and the doctor are responsible for the final decision. [3] In the Indian health care scenario, the concept of shared decision-making has to be considered in the cultural and literacy aspects. A qualitative study and ethical analysis on Healthcare Decision Making in Rural India, a decade ago brought to light, the glaring differences between shared decision making in the Western world and India.…”
Section: Introductionmentioning
confidence: 99%